2016
DOI: 10.1016/j.intacc.2016.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Discussion of “Security Returns and Volume Responses around International Financial Reporting Standards (IFRS) Earnings Announcements”

Abstract: Olibe (2016) uses price and trading volume responses around IFRS earnings disclosures for U.K. cross-listed firms trading as American Depository Receipts in U.S. equity markets to investigate whether such disclosures provide information to market participants over and above U.S. GAAP earnings disclosures. He finds evidence of significant price and trading volume responses for IFRS earnings disclosures, leading to the conclusion that market participants find that those disclosures facilitate trading in U.S. equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The study further reveals that the immediate price reaction over the 3 -day announcement window on average is 41.8% for IFRS earning news whereas it is about 71% for US GAAP earnings disclosure. The implication is that IFRS is sufficient to support the production of information that investors are apparently willing to use (see also (Perkins, 2016); (Olibe, 2016a). (Ali, Akbar, & Ormrod, 2016) examined the impact of changes from UK GAAP to IFRS on companies listed on the Alternative Investment Market (AIM) in the UK, using Gray's partial analysis estimates, and observed that on the average profit reported under the IFRS is quiet higher than those reported under UK GAAP.…”
Section: Introductionmentioning
confidence: 99%
“…The study further reveals that the immediate price reaction over the 3 -day announcement window on average is 41.8% for IFRS earning news whereas it is about 71% for US GAAP earnings disclosure. The implication is that IFRS is sufficient to support the production of information that investors are apparently willing to use (see also (Perkins, 2016); (Olibe, 2016a). (Ali, Akbar, & Ormrod, 2016) examined the impact of changes from UK GAAP to IFRS on companies listed on the Alternative Investment Market (AIM) in the UK, using Gray's partial analysis estimates, and observed that on the average profit reported under the IFRS is quiet higher than those reported under UK GAAP.…”
Section: Introductionmentioning
confidence: 99%